Socio-Economic Study of Bote Community People - A Case Study of Darchha Village Development Committee of Palpa District - Gautam, Shanta (Cognition, 2021)
The expected solution of this research was to identification the level of socio-economic condition of Bote community in study area. The case study was made using narrative and content analysis and some quantitative data were analyzed using simple statistical tools. The study reflect from the community about economic components was not more optimistic. They are considered as Hindu ethnic groups because they worship the holy cow and use its urine (gaut). They have been celebrating all Hindu festival such as Dashain, Tihar, Maghe Sankranti etc. their socio-economic and cultural system is adopted from the Arians and they belong to Matawali caste in the low social hierarchy. They still believe in mystical things like Sikari Pooja, Bayu Pooja etc. and .wearing typical dress .The settlement patterns was found differ them from other ethnic group. The literacy rate is very low. More than 90% households have been suffering from alcoholism. It seems to be the root cause of their backwardness. Some of them even sell goods from their houses to get money of alcohol. As a result of alcoholism, they do not have saving habit and many of them are under debt.